Change in Substance Use and the Effects of Social Distancing on Health-Related Quality of Life and Depressive Symptoms During the COVID-19 Pandemic in People Living With and Without HIV. (1st November 2022) - Schaaf, Reja E. A.; Verburgh, Myrthe L.; Boyd, Anders; Wit, Ferdinand W.; Nieuwkerk, Pythia T.; Schim van der Loeff, Maarten F.; Reiss, Peter; ,
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: Little is known about the impact of social distancing on health-related quality of life and depressive symptoms in older people with HIV during the COVID-19 pandemic. Setting: HIV-positive and HIV-negative AGEh IV Cohort Study participants. Method: In September-November 2020, participants completed questionnaires on social distancing, change in substance use, health-related quality of life (EQ-6D, including EQ-VAS), and depressive symptoms (PHQ-9). Associations between social distancing and (1) EQ-VAS or (2) PHQ-9 score ≥10 (clinically relevant depressive symptoms) were analyzed using fractional and binomial logistic regression, respectively. Results: Two hundred fourteen HIV-positive and 285 HIV-negative participants were analyzed. 77.4% found social distancing important and 66.9% reported good adherence to these measures, without significant differences between HIV-positive and HIV-negative participants. In both groups, <5% reported increased smoking or recreational drug use, but more HIV-positive (12.2%) than HIV-negative (4.9%) participants ( P = 0.005) reported increased/more frequent alcohol use. Median EQ-VAS was slightly lower in HIV-positive (80 IQR = 73–90) than HIV-negative (84 IQR = 75–90) participants ( P = 0.041). The prevalence of clinically relevant depressive symptoms was similar (HIV-positive, 8.4% and HIV-negative, 8.8%). Worrying about contracting COVID-19 and having ≥3 (vs no) comorbidities were associated with lower EQ-VAS and finding social distancing easy with higher EQ-VAS. Worrying about contracting COVID-19 and younger than 60 years (vs ≥65) were associated with higher odds of clinically relevant depressive symptoms. HIV status was associated with neither outcome. Conclusions: Initially during the COVID-19 pandemic in the Netherlands, a similar majority of HIV-positive and HIV-negative participants reported adhering to social distancing. Irrespective of HIV status, concerns about contracting COVID-19 negatively affected participants' perceived current health and increased risk of depressive symptoms.